PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA SUBTEMA KEBERAGAMAN BUDAYA BANGSAKU - Nurhasanah; Suhendra; Rini Sri indriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The influence of the implementation of problem based learning model on student learning outcomes subtheme of my nation’s cultular diversity. This study uses a two group design quasi experimental approach at Leuwisadeng elementary school. The subject of this study were student in grades IV-A and IV-B of Leuwisadeng state elementary school with a total of 59 student. This research was conducted in the odd semester of the 2022/2023 academic year. The results of this study indicate that there is a effect of the application of the problem based learning model on student learning outcomes in subtheme 1 of the cultural diversity of my nation. This can be seen from the N-gain value in the experimental class group which has an average value of 69, while in the control class the average is 48. In the results of hypothesis testing that have been carried out are that HO is rejected an Ha is accepted because tcount (4.91) > ttabel (200247). Thus, the result of the research that have been carried out can be concluded that the application of the problem based learning model has a positive influence on student learning outcomes in subtheme 1 cultural disversity of my nation.